2019
DOI: 10.1021/acsmaterialslett.9b00116
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Assembly, and Function of (Latent)-Chiral AIEgens

Abstract: The discovery of the photophysical phenomenon of aggregation-induced emission (AIE) by Tang in 2001 has drawn intense attention of scientists all over the world and created potential applications in various areas, such as biological probes, chemical sensors, and optoelectronic devices. Incorporation of AIE with chirality is a pioneering attempt to broaden the field of AIE research. Generally, chiral AIEgens are designed by attaching chiral units to an AIE-active building block. From another point of view, AIEg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 69 publications
0
47
0
1
Order By: Relevance
“…Stereogenic centers and chiral additives are usually necessary to induce an asymmetric arrangement of molecules to form helical assemblies. However, at the aggregate level, the achiral AIEgen itself can even form helical assemblies without incorporating any chiral additives or external stimuli . For example, in TPE crystals, the four phenyl peripheries can rotate in clockwise or anticlockwise directions to form M or P configurations, respectively, to achieve the transformation from achiral to chiral (Figure a,b) .…”
Section: Aie and The Research Branchesmentioning
confidence: 99%
“…Stereogenic centers and chiral additives are usually necessary to induce an asymmetric arrangement of molecules to form helical assemblies. However, at the aggregate level, the achiral AIEgen itself can even form helical assemblies without incorporating any chiral additives or external stimuli . For example, in TPE crystals, the four phenyl peripheries can rotate in clockwise or anticlockwise directions to form M or P configurations, respectively, to achieve the transformation from achiral to chiral (Figure a,b) .…”
Section: Aie and The Research Branchesmentioning
confidence: 99%
“…[125][126][127] Tetraphenylethylene (TPE) is one of the most studied AIEgens and its isolated molecules are achiral because of the free rotation of the four phenyl rings, as reflected by the silent CD signal of its solution. [128][129][130] However, in 2011, Zhang et al observed a pair of inverse CD spectra from two TPE crystals ( Figure 5). [131] Crystallographic analysis proved that these two crystals, namely, M-TPE and P-TPE, were enantiomorphs.…”
Section: Static Aggregatesmentioning
confidence: 99%
“…The pyrene-modified CPP had both cyclic and planar π-conjugated structures in its structure, and tetraphenylethene (TPE)-functionalized CPP was incorporated with both cyclic and nonplanar structures, whereas carboxyl-modified CPP possessed both hydrophilic and hydrophobic moieties in the molecule. 38,39 These CPPs are referred to as [8]CPP, [8]CPPpyrene, [8]CPP-TPE, and [8]CPP-COOH, respectively.…”
Section: Resultsmentioning
confidence: 99%